Peran Koridor Hijau Perkotaan dalam Meningkatkan Kenyamanan Termal: Studi pada Kota-Kota Menengah Beriklim Tropis di Indonesia - Nabila Sekar Arumi; Aditya Farhan; Dea Aprilia (Trends Research of Environmental Studies, 2026)
Increasing urban temperatures and the urban heat island phenomenon have become major challenges for medium-sized cities located in tropical climates in Indonesia. These conditions reduce outdoor thermal comfort and affect the quality of the urban environment. This study aims to analyze the role of urban green corridors in improving thermal comfort in medium-sized tropical cities in Indonesia. A quantitative descriptive approach was employed through a review of empirical findings regarding the effects of vegetation, green open spaces, and ventilation corridors on urban microclimatic conditions. The analysis focused on the relationship between green corridor characteristics and changes in air temperature, relative humidity, and thermal comfort conditions. The results indicate that urban green corridors contribute to mitigating excessive heat through shading effects, enhanced evapotranspiration, and improved air circulation. The integration of green corridors with green open spaces and urban ventilation corridors provides significant benefits for enhancing thermal comfort in tropical urban areas. These findings highlight the importance of incorporating green corridors into climate adaptation strategies and sustainable urban planning for medium-sized cities in Indonesia.